CaCl26H2O / COF / PAE composite phase change material and preparation method thereof
Through the design and preparation of CaCl2·6H2O/COF/PAE composite phase change material, the problem of liquid phase leakage during the phase change process is solved, and the effect of high energy storage capacity and low leakage is achieved. It is suitable for medium and low temperature phase change energy storage applications.
Patent Information
- Application Number
- CN202510095897.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-22
AI Technical Summary
Hydrated inorganic salts, as inorganic phase change materials, have liquid phase leakage problems during the phase change process, affecting the heat storage efficiency and causing damage to the use environment.
The polyacrylate porous material PAE was prepared by emulsion polymerization, and the covalent organic frame material COF was grown in situ in its pores to form the COF/PAE composite material as a carrier, and the calcium chloride hexahydrate CaCl2·6H2O was filled to form the composite phase change material.
It effectively prevents the supercooling of CaCl2·6H2O, enhances the energy storage capacity of phase change materials, reduces liquid phase leakage, and improves the circulation stability and thermal energy utilization efficiency of the material.
Smart Images

Figure CN119875589A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phase change materials, in particular to a CaCl2·6H2O / COF / PAE composite phase change material and a preparation method thereof. Background Art
[0002] Inorganic phase change materials have been widely used in the field of energy storage due to their high phase change latent heat, excellent thermal conductivity and chemical stability. In particular, hydrated inorganic salts, such as calcium chloride hexahydrate (CaCl2·6H2O), have good application prospects in building energy conservation, solar thermal storage and refrigeration insulation due to their moderate phase change temperature (about 29°C) and high latent heat value. However, hydrated inorganic salts will change from solid to liquid during the phase change process, resulting in the problem of liquid phase leakage in phase change materials. Liquid phase leakage not only affects the heat storage efficiency, but also damages the use environment.
[0003] In order to deal with the problem of liquid phase leakage, researchers usually use porous matrix materials to encapsulate inorganic phase change materials. Commonly used porous materials such as expanded perlite, diatomaceous earth, mesoporous silica, etc., these materials provide capillary force through the pore structure, can effectively adsorb inorganic phase change materials, and reduce the leakage of liquid during the phase change process. In addition, the use of porous matrix materials can also effectively improve the thermal cycling stability of inorganic phase change materials. However, although the micropores of porous materials have strong capillary action and can effectively prevent the leakage of phase change materials, their excessively small pore size often limits the phase change behavior of inorganic phase change materials, resulting in a decrease in their latent heat value. On the other hand, although mesoporous materials provide sufficient phase change space, their specific surface area is relatively small and the capillary force is insufficient. In long-term cyclic use, the problem of liquid phase leakage still exists.
[0004] Therefore, developing a porous matrix material that can provide sufficient phase change space and possess appropriate capillary force is of great significance for the energy storage application of inorganic phase change materials. Summary of the invention
[0005] The purpose of the present invention is to provide a CaCl2·6H2O / COF / PAE composite phase change material and a preparation method thereof, and to utilize the confined space of different pore sizes of the material to constrain the heterogeneous nucleation process of the liquid phase, so as to solve the problems that the current hydrated inorganic salt as an inorganic phase change material has a serious overcooling phenomenon and the phase change material has a small energy storage capacity and is prone to leakage due to insufficient phase change space or weak capillary force after encapsulation of organic materials.
[0006] The present invention is specifically achieved through the following technical scheme. According to a CaCl2·6H2O / COF / PAE composite phase change material proposed in the present invention, it is composed of calcium chloride hexahydrate (CaCl2·6H2O), a covalent organic framework material (COF) and a polyacrylate porous material (PAE). The polyacrylate porous material PAE is a spherical particle with a rich porous structure inside. The covalent organic framework material (COF) is distributed in the pores of the polyacrylate porous material (PAE) to form a COF / PAE composite material. The COF / PAE composite material is used as a carrier, and the calcium chloride hexahydrate phase change material is filled in the pores of the carrier to form a CaCl2·6H2O / COF / PAE composite phase change material.
[0007] The present invention also provides a method for preparing a CaCl2·6H2O / COF / PAE composite phase change material, which comprises the following steps: (1) Preparation of polyacrylate porous material PAE Glycidyl methacrylate, trimethylolpropane triacrylate, PEG-PPG-PEG, and benzoyl peroxide were dissolved in toluene, and mixed evenly in an ultrasonic chemical reactor at room temperature to form an oil phase; Under stirring conditions, ethylenediamine and ethylene glycol are dissolved in water as the aqueous phase, the obtained oil phase is placed in an ice-water bath, and then the aqueous phase is added dropwise to the above oil phase, and stirred for 1 hour to form a uniform and stable oil-in-water emulsion; nitrogen is introduced into the oil-in-water emulsion, and then N,N-dimethylaniline is added thereto, and stirred for reaction for 5-10 minutes, and then ammonium persulfate and polyvinyl alcohol are added thereto, and stirred for reaction for 1 hour, and then tetramethylethylenediamine is added dropwise to the reaction system, and stirred for reaction at 55 °C and 400-500 rpm for 20-30 minutes to ensure that the emulsion of the reaction system is dispersed into uniform droplets. At this time, the monomers in the reaction system begin to polymerize to form white solid particles of polyacrylate. When the white solid particles are no longer generated, the stirring is stopped, and the mixture is kept at 55 °C for 30-60 minutes, and then the reaction mixture is filtered, and the filtrate is dried to obtain a polyacrylate porous material PAE; (2) Preparation of COF / PAE composite carrier Add p-toluenesulfonic acid monohydrate and trialdehyde phloroglucinol into deionized water and mix and stir to obtain an organic ligand dispersion; add polyacrylate porous material PAE into the organic ligand dispersion and stir evenly to obtain a mixed dispersion; add diaminoanthraquinone to the mixed dispersion, mix evenly, and stir at 120° C. to make it fully react; after the reaction is completed, centrifuge and separate, and dry the product at 65° C. to obtain a COF / PAE composite carrier; (3) Preparation of CaCl2·6H2O / COF / PAE composite phase change material A certain mass of CaCl2·6H2O crystals was melted at 50 °C to obtain CaCl2 molten liquid. The CaCl2 molten liquid was slowly added to the COF / PAE composite carrier in a vacuum environment and stirred for 30-40 min in the vacuum environment. The obtained composite material was placed in a vacuum drying oven and dried to obtain the CaCl2·6H2O / COF / PAE composite phase change material.
[0008] The preparation method of the aforementioned CaCl2·6H2O / COF / PAE composite phase change material, in step (1), the volume ratio of the water phase to the oil phase is 2:5; the mass ratio of glycidyl methacrylate, trimethylolpropane triacrylate, PEG-PPG-PEG, and benzoyl peroxide is 3:1:1:1; the mass ratio of ethylenediamine to ethylene glycol is 7:9, and the ratio of the total mass of ethylenediamine and ethylene glycol to the total mass of glycidyl methacrylate, trimethylolpropane triacrylate, PEG-PPG-PEG, and benzoyl peroxide is 2:15; the ratio of the mass of ammonium persulfate to the total mass of glycidyl methacrylate, trimethylolpropane triacrylate, PEG-PPG-PEG, and benzoyl peroxide is 1:20, and the ratio of the mass of polyvinyl alcohol to the total mass of glycidyl methacrylate, trimethylolpropane triacrylate, PEG-PPG-PEG, and benzoyl peroxide is 1:5.
[0009] In the aforementioned method for preparing the CaCl2·6H2O / COF / PAE composite phase change material, in step (2), the mass ratio of p-toluenesulfonic acid monohydrate to trialdehyde phloroglucinol is 23:6; the mass fraction of the polyacrylate porous material PAE in the mixed dispersion is 25-35%; and the mass ratio of diaminoanthraquinone to trialdehyde phloroglucinol is 1:2.
[0010] In the aforementioned method for preparing the CaCl2·6H2O / COF / PAE composite phase change material, step (3) can prepare CaCl2·6H2O / COF / PAE composite phase change materials containing different mass fractions of CaCl2·6H2O according to the different masses of CaCl2·6H2O crystals.
[0011] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages: (1) The present invention uses emulsion polymerization to prepare polyacrylate porous material PAE as the matrix of the composite phase change material. The polyacrylate porous material PAE is a spherical particle with a rich porous structure inside. The organic framework COF material is in situ grown in the pores of the polyacrylate porous material PAE by an in-situ growth method to form a COF / PAE composite material. The COF / PAE composite material is used as a composite carrier, and the inorganic phase change material calcium chloride hexahydrate (CaCl2·6H2O) is adsorbed in the pores of the COF / PAE composite carrier by vacuum impregnation. The tertiary porous structure of the polyacrylate porous material PAE provides a good place and support for the growth of the organic framework COF material, avoiding the rapid decrease in specific surface area caused by the volume pressure of the organic framework COF material powder. The high specific surface area and capillary force of the organic framework COF material can achieve high loading and low leakage of calcium chloride hexahydrate.
[0012] (2) In the preparation process of the polyacrylate porous material PAE, the present invention optimizes the oil phase components, the water-oil phase ratio and the selection of the emulsifier by the emulsion precipitation polymerization method to regulate the composition and interfacial tension of the emulsion. Combined with the precise control of the reaction temperature and reaction time, the pore structure of the polyacrylate porous material PAE is regulated. The polyacrylate porous material PAE prepared by the above method has a specific network structure, exhibits excellent hydrophilic adsorption characteristics, and can be combined with the organic framework COF material to form a composite carrier with a multi-level pore structure. Through the in-situ loading method, the organic framework COF material is directly grown in the pores of the polyacrylate porous material PAE, forming a layer of dense COF grains on the surface of the macropores, thereby achieving a close combination of the polyacrylate porous material PAE and the organic framework COF material, thereby avoiding the accumulation of COF materials leading to a significant reduction in specific surface area. When CaCl2·6H2O is loaded on this composite carrier with a multi-level pore structure, the synergistic effect of the mesopores of polyacrylate and the micropores of COF material is shown: on the one hand, the pore size restriction of the micro-mesoporous composite material can effectively slow down the supercooling phenomenon of CaCl2·6H2O; on the other hand, the microporous structure of the COF material provides a large specific surface area, which produces a strong capillary effect during the phase change process and effectively prevents the leakage of CaCl2·6H2O. In addition, the mesoporous structure of polyacrylate provides sufficient space for the phase change process of CaCl2·6H2O, thereby ensuring the smooth progress of the phase change behavior, effectively improving the phase change enthalpy value of CaCl2·6H2O, and enhancing the energy storage capacity.
[0013] (3) The present invention can improve the specific heat capacity and thermal conductivity of the material through the innovatively designed phase change material structure, so that it can quickly absorb and release heat, greatly improving the heat storage capacity of the material. By adopting an improved formula, the aging and performance degradation of the material during the phase change process are delayed, ensuring that the material can still maintain excellent heat storage effects in multiple phase change cycles, thereby extending the service life of the material. The composite phase change material prepared by the present invention can respond quickly to temperature changes and quickly complete phase changes during heating or cooling, thereby improving the utilization efficiency of thermal energy and the dynamic response speed.
[0014] (4) The present invention uses environmentally friendly and non-toxic raw materials, so that the phase change heat storage material will not cause pollution to the environment during production, use and disposal, which meets the requirements of green and sustainable development. By improving the production process, simplifying the production process, and reducing the production cost of the material, the present invention can improve economic benefits and reduce energy waste through heat recovery and reuse in practical applications.
[0015] (5) The present invention uses the COF / PAE composite material as a carrier with a multi-level pore structure to adsorb CaCl2·6H2O, which not only provides sufficient phase change space for the phase change material, but also significantly increases the energy storage capacity of CaCl2·6H2O and reduces leakage. At the same time, due to the pore size restriction effect of the micro-mesoporous composite material, the supercooling phenomenon of CaCl2·6H2O is effectively reduced, so that it can be applied to medium and low temperature phase change energy storage, maintaining stable phase change behavior in a variety of environments and temperature ranges, and is suitable for a wide range of heat storage scenarios, including building heating, industrial waste heat recovery, renewable energy storage, etc., to meet the needs of different fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is the mechanism diagram of the preparation of CaCl2·6H2O / COF / PAE composite phase change material; Figure 2 is a SEM image of the COF / PAE composite support prepared in Example 1; Figure 3 is a SEM image of the CaCl2·6H2O / COF / PAE composite phase change material prepared in Example 1; Figure 4 It is the DSC graph of the CaCl2·6H2O phase change material and the CaCl2·6H2O / COF / PAE composite phase change material prepared in Example 1; Figure 5 is a DSC graph of the CaCl2·6H2O / COF / PAE composite phase change material prepared in Example 1 after 100 cycles; Figure 6It is a comparison diagram of the leakage after heating of the CaCl2·6H2O phase change material and the CaCl2·6H2O / COF / PAE composite phase change material prepared in Example 1. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The present invention is described in detail with specific examples below. If no specific conditions are specified in the following examples, they are all carried out according to conventional conditions or conditions recommended by the manufacturer. The raw materials and reagents used without specifying the manufacturer are all conventional products that can be purchased from the market.
[0021] Embodiment 1: Step (1): Preparation of polyacrylate porous material (PAE) Step (1.1): dissolve 3 g of glycidyl methacrylate, 1 g of trimethylolpropane triacrylate, 1 g of PEG-PPG-PEG, and 1 g of benzoyl peroxide in 10 mL of toluene, and mix them uniformly using an ultrasonic chemical reactor at room temperature to form an oil phase; Step (1.2): Under stirring conditions, 0.35 g of ethylenediamine and 0.45 g of ethylene glycol were dissolved in 4 mL of water as the aqueous phase, the oil phase of step (1.1) was placed in an ice-water bath (about 5°C), and then the aqueous phase was added dropwise to the oil phase and stirred for 1 h to form a uniform and stable oil-in-water emulsion; Step (1.3): nitrogen is introduced into the water-in-oil emulsion of step (1.2) to prevent oxygen in the air from affecting the polymerization reaction in the emulsion, and then 4 drops (about 0.2 mL) of reducing agent N,N-dimethylaniline are added thereto, and stirred for 5-10 min to promote the subsequent polymerization reaction; then 0.3 g of oxidizing agent ammonium persulfate and 1.2 g of dispersing agent polyvinyl alcohol are added to stabilize the emulsion structure, and after stirring for 1 h, 6-8 drops of reducing agent tetramethylethylenediamine are added to the reaction system, and stirred at 55°C and 400-500rpm for 20-30 min to ensure that the emulsion of the reaction system is dispersed into uniform droplets. At this time, the monomers in the reaction system begin to polymerize to form white solid particles of polyacrylate. When the white solid particles are no longer generated, stirring is stopped, and the mixture is kept at 55°C for 30 min to complete the polymerization reaction of the monomers. Then, the reaction mixture is filtered, and the filtrate is dried to obtain a polyacrylate porous material (PAE); Step (2): Preparation of COF / PAE composite carrier Step (2.1): Add 230 mg of p-toluenesulfonic acid monohydrate PTSA and 60 mg of trialdehyde phloroglucinol Dq into 10 mL of deionized water and stir for 5 min to obtain an organic ligand dispersion; Step (2.2): taking a certain mass of the polyacrylate porous material (PAE) prepared in step (1) and adding it to the organic ligand dispersion prepared in step (2.1), stirring evenly to obtain a mixed dispersion, wherein the mass fraction of the polyacrylate porous material (PAE) in the mixed dispersion is 25%; Step (2.3): Add 30 mg of diaminoanthraquinone Tp to the mixed dispersion prepared in step (2.2), mix well, and stir at 120°C for 18 h to allow it to react fully; after the reaction is completed, centrifuge and separate the product, and dry it in an oven at 65°C for 24 h to obtain a COF / PAE composite carrier.
[0022] Step (3): Preparation of CaCl2·6H2O / COF / PAE composite phase change material 0.5 g of CaCl2·6H2O was melted in an oven at 50 °C to obtain a CaCl2 molten liquid. The CaCl2 molten liquid was slowly added to the COF / PAE composite support prepared in step (2) in a vacuum environment, and stirred for 30 min in the vacuum environment. The resulting composite material was placed in a vacuum drying oven at 30 °C and dried for 5 h to obtain a CaCl2·6H2O / COF / PAE composite phase change material. The mass of the COF / PAE composite support before the addition of the CaCl2 molten liquid was weighed, recorded as m1, and the mass of the final CaCl2·6H2O / COF / PAE composite phase change material was weighed, recorded as m2. The mass fraction w of CaCl2·6H2O in the CaCl2·6H2O / COF / PAE composite phase change material was calculated by the formula w=((m2-m1) / m2)×100% to be 50% (the same below).
[0023] Example 2 Step (2.2): taking a certain mass of the polyacrylate porous material (PAE) prepared in step (1) and adding it to the organic ligand dispersion prepared in step (2.1), stirring evenly to obtain a mixed dispersion, wherein the mass fraction of the polyacrylate porous material in the mixed dispersion is 30%; the remaining steps are the same as in Example 1.
[0024] Example 3 Step (2.2): taking a certain mass of the polyacrylate porous material (PAE) prepared in step (1) and adding it to the organic ligand dispersion prepared in step (2.1), stirring evenly to obtain a mixed dispersion, wherein the mass fraction of the polyacrylate porous material in the mixed dispersion is 35%; the remaining steps are the same as in Example 1.
[0025] Example 4 The mass of CaCl2·6H2O in step (3) is 0.35 g, and the remaining steps are the same as in Example 1. The mass fraction of CaCl2·6H2O in the CaCl2·6H2O / COF / PAE composite phase change material of this embodiment is obtained by the calculation method of Example 1, which is 40%.
[0026] Example 5 The mass of CaCl2·6H2O in step (3) is 0.45 g, and the remaining steps are the same as those in Example 2. The mass fraction of CaCl2·6H2O in the CaCl2·6H2O / COF / PAE composite phase change material of this example is obtained by the calculation method of Example 1, which is 48%.
[0027] Example 6 The mass of CaCl2·6H2O in step (3) is 0.6 g, and the remaining steps are the same as those in Example 3. The mass fraction of CaCl2·6H2O in the CaCl2·6H2O / COF / PAE composite phase change material of this example is 55% as calculated by the calculation method of Example 1.
[0028] Figure 1 This is a mechanism diagram for the preparation of CaCl2·6H2O / COF / PAE composite phase change material.
[0029] Figure 2 is a SEM image of the COF / PAE composite carrier prepared in Example 1. Figure 2 It can be seen that the prepared COF / PAE composite carrier is a spherical structure with uniform morphology, and the COF material is evenly distributed on the surface and gaps of PAE.
[0030] Figure 3 This is an SEM image of the CaCl2·6H2O / COF / PAE composite phase change material prepared in Example 1. It can be seen that CaCl2·6H2O is uniformly loaded inside and on the surface of the COF / PAE composite carrier, effectively realizing the encapsulation of the CaCl2·6H2O phase change material by COF / PAE.
[0031] Figure 4This is the DSC graph of the CaCl2·6H2O / COF / PAE composite phase change material prepared in Example 1. It can be seen that the CaCl2·6H2O / COF / PAE composite material shows a decrease in supercooling compared to the single CaCl2·6H2O, that is, the difference ΔT between the melting temperature and the crystallization temperature is reduced. The crystallization temperature of CaCl2·6H2O is 19°C, the melting temperature is 34°C, and the difference ΔT between the melting temperature and the crystallization temperature is 15°C. The crystallization temperature of the CaCl2·6H2O / COF / PAE composite phase change material is about 22°C, the melting temperature is 32°C, and the difference ΔT between the melting temperature and the crystallization temperature is 10°C. The supercooling of the CaCl2·6H2O / COF / PAE composite phase change material is 5°C lower than that of the single CaCl2·6H2O, which indicates that the COF / PAE composite carrier effectively reduces the supercooling phenomenon of CaCl2·6H2O, enhances the cycle stability and heat release efficiency of the phase change material, and makes it more suitable for stable thermal energy storage and release.
[0032] Figure 5 This is the DSC graph of the CaCl2·6H2O / COF / PAE composite phase change material prepared in Example 1 after 100 cycles. It can be seen that compared with the uncycled CaCl2·6H2O / COF / PAE composite phase change material, the CaCl2·6H2O / COF / PAE composite phase change material maintains a stable phase change temperature and good heat storage capacity after 100 cycles. Although the latent heat is slightly reduced after 100 cycles, the overall thermal performance of the material remains good, and it is suitable for phase change energy storage materials in practical applications.
[0033] Table 1 shows the melting latent heat of the CaCl2·6H2O / COF / PAE composite phase change material prepared in Example 1 after multiple cycles. It can be seen that after 100 cycles of CaCl2·6H2O / COF / PAE, the melting latent heat changes from 86.43 J / g at the beginning to 80.41 J / g, indicating that the CaCl2·6H2O / COF / PAE composite phase change material has good thermal reliability.
[0034] Table 1. Latent heat of melting of CaCl2·6H2O / COF / PAE composite phase change materials after multiple cycles Figure 61 is a comparison diagram of the leakage of CaCl2·6H2O and the CaCl2·6H2O / COF / PAE composite phase change material prepared in Example 1 after heating, wherein (a) represents unheated CaCl2·6H2O, (b) represents the situation after CaCl2·6H2O is heated at 40°C for 30 min, (c) represents the unheated CaCl2·6H2O / COF / PAE composite phase change material, and (d) represents the situation after CaCl2·6H2O / COF / PAE composite phase change material is heated at 40°C for 30 min. It can be seen that compared with single CaCl2·6H2O, after being coated with the COF / PAE porous structure, the leakage of the CaCl2·6H2O / COF / PAE composite phase change material is significantly reduced, indicating that the preparation method of the present invention can significantly reduce the liquid phase leakage problem of the phase change material after the composite phase change material is encapsulated with CaCl2·6H2O.
[0035] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made to the above embodiments by any technician familiar with the profession according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A CaCl2·6H2O / COF / PAE composite phase change material, characterized in that: The invention is composed of calcium chloride hexahydrate, an organic framework COF material and a polyacrylate porous material PAE. The polyacrylate porous material PAE is a spherical particle with a rich porous structure inside. The organic framework COF material is distributed in the pores of the polyacrylate porous material PAE to form a COF / PAE composite material. The COF / PAE composite material is used as a carrier, and the calcium chloride hexahydrate phase change material is filled in the pores of the carrier to form a CaCl2·6H2O / COF / PAE composite phase change material.
2. A method for preparing a CaCl2·6H2O / COF / PAE composite phase change material, characterized in that: The following steps are involved: (1) Preparation of polyacrylate porous material PAE Glycidyl methacrylate, trimethylolpropane triacrylate, PEG-PPG-PEG, and benzoyl peroxide were dissolved in toluene, and mixed evenly in an ultrasonic chemical reactor at room temperature to form an oil phase; Under stirring conditions, ethylenediamine and ethylene glycol are dissolved in water as the aqueous phase, the obtained oil phase is placed in an ice-water bath, and then the aqueous phase is added dropwise to the above oil phase, and stirred for 1 hour to form a uniform and stable oil-in-water emulsion; nitrogen is introduced into the oil-in-water emulsion, and then N,N-dimethylaniline is added thereto, and stirred for reaction for 5-10 minutes, and then ammonium persulfate and polyvinyl alcohol are added thereto, and stirred for reaction for 1 hour, and then tetramethylethylenediamine is added dropwise to the reaction system, and stirred for reaction at 55 °C and 400-500 rpm for 20-30 minutes to ensure that the emulsion of the reaction system is dispersed into uniform droplets. At this time, the monomers in the reaction system begin to polymerize to form white solid particles of polyacrylate. When the white solid particles are no longer generated, the stirring is stopped, and the mixture is kept at 55 °C for 30-60 minutes, and then the reaction mixture is filtered, and the filtrate is dried to obtain a polyacrylate porous material PAE; (2) Preparation of COF / PAE composite carrier Add p-toluenesulfonic acid monohydrate and trialdehyde phloroglucinol into deionized water and mix and stir to obtain an organic ligand dispersion; add the polyacrylate porous material PAE prepared in step (1) into the organic ligand dispersion and stir evenly to obtain a mixed dispersion; add diaminoanthraquinone to the mixed dispersion, mix evenly, and stir at 120° C. to allow it to react fully; after the reaction is completed, centrifuge and separate, and dry the product at 65° C. to obtain a COF / PAE composite carrier; (3) Preparation of CaCl2·6H2O / COF / PAE composite phase change material A certain mass of CaCl2·6H2O crystals was melted at 50 °C to obtain CaCl2 molten liquid. The CaCl2 molten liquid was slowly added to the COF / PAE composite carrier in a vacuum environment and stirred for 30-40 min in the vacuum environment. The obtained composite material was placed in a vacuum drying oven and dried to obtain the CaCl2·6H2O / COF / PAE composite phase change material.
3. The method for preparing the CaCl2·6H2O / COF / PAE composite phase change material according to claim 2, characterized in that: In step (1), the volume ratio of the water phase to the oil phase is 2:
5.
4. The method for preparing the CaCl2·6H2O / COF / PAE composite phase change material according to claim 2, characterized in that: In step (1), the mass ratio of glycidyl methacrylate, trimethylolpropane triacrylate, PEG-PPG-PEG and benzoyl peroxide is 3:1:1:
1.
5. The method for preparing the CaCl2·6H2O / COF / PAE composite phase change material according to claim 2 or 4, characterized in that: In step (1), the mass ratio of ethylenediamine to ethylene glycol is 7:9, and the ratio of the total mass of ethylenediamine and ethylene glycol to the total mass of glycidyl methacrylate, trimethylolpropane triacrylate, PEG-PPG-PEG, and benzoyl peroxide is 2:
15.
6. The method for preparing the CaCl2·6H2O / COF / PAE composite phase change material according to claim 2 or 4, characterized in that: In step (1), the ratio of the mass of ammonium persulfate to the total mass of glycidyl methacrylate, trimethylolpropane triacrylate, PEG-PPG-PEG, and benzoyl peroxide is 1:20, and the ratio of the mass of polyvinyl alcohol to the total mass of glycidyl methacrylate, trimethylolpropane triacrylate, PEG-PPG-PEG, and benzoyl peroxide is 1:
5.
7. The method for preparing the CaCl2·6H2O / COF / PAE composite phase change material according to claim 2, characterized in that: In step (2), the mass ratio of p-toluenesulfonic acid monohydrate to trialdehyde phloroglucinol is 23:6; and the mass fraction of the polyacrylate porous material PAE in the mixed dispersion is 25-35%.
8. The method for preparing the CaCl2·6H2O / COF / PAE composite phase change material according to claim 2, characterized in that: In step (2), the mass ratio of diaminoanthraquinone to trialdehyde phloroglucinol is 1:
2.
9. The method for preparing the CaCl2·6H2O / COF / PAE composite phase change material according to claim 2, characterized in that: Step (3) According to the different masses of CaCl2·6H2O crystals, CaCl2·6H2O / COF / PAE composite phase change materials containing different mass fractions of CaCl2·6H2O are prepared.
Citation Information
Patent Citations
Preparation method of metal organic framework based composite phase-change material
CN103756646A
Preparation method of network porous polymer-based composite phase-change material
CN104818001A
COF-containing composite material, heat storage / release member, method for producing said composite material, and COF single crystal and method for producing same
CN115427533A
Polyacrylate microspheres and application thereof
CN116478326A
Preparation method of phase change heat storage particles
CN117965139A